ASTER Mineral Classification for Regolith Mapping in Tick Hill Mount Isa, Northwest Queensland - Fitri Agustin (Indonesian Journal on Geoscience, 2017)
DOI: 10.17014/ijog.4.2.97-109This paper analyzed the mineral maps of AlOH bearing minerals and iron oxide using ASTER imagery in Tick Hill, Mount Isa, northwestern part of Queensland, as a guide for mapping the regolith unit within the area. Tick Hill is part of the Proterozoic Eastern and Western Fold Belt Province (Mount Isa Inlier Complex) covered by Mesozoic and Paleozoic lithologies and dominated by medium to coarse hornblende-biotite granite and gneiss; both of which intruded during 1760 - 1720 Ma. Highly weathered landforms cover the whole area. The Mesozoic sediments have experienced deep weathering, and currently present in the form of mesas. The weathering profiles are dominated by kaolinite, smectite, and pedogenic carbonates with some secondary silicification. Part of the landform is covered by colluvium varying in thickness from less than 1 m up to 12 m in certain places. Digital image processing has been done to ASTER imagery, i.e: calibrating, mosaicing, and band ratioing and false colour RGB. Within these methods, iron oxide, kaolinite, AlOH, and MgOH group mineral maps have successfully been created through the ASTER imagery. Later, these mineral maps were applied to interpret the surface regolith mapping unit. In addition, field samples have been taken in regolith covered areas to validate the ASTER mineral information.